O posicionamento da mídia paulista em relação ao governo Temer - Guerra, Carolina Maria Fernandes (2020)
The text analyzes the editorial stances of the newspapers O Estado de S. Paulo and Folha de S. Paulo during the Temer government, from May 2016 to December 2018. The study examines the editorial positions of the newspapers towards the president, his relations with Congress and the advancement of the main elements of his agenda: the labor reform, the pension reform and the spending ceiling. It also analyzes the newspapers’ stances regarding the corruption cases that implicated Temer. The macro objective of this study, on the other hand, was to analyze how the turbulences in the political field in the Temer period reflected in the positioning of the media when covering the advance of the government's economic agendas